Development of Interactive Learning Media Based on Wordwall in Science Learning at ELementary School - Wapuah; Hartono; Prasetyo, Danang (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to develop interactive learning media based on Wordwall in the subject of science for grade IV at SD Negeri Jatiwates 1 Jombang. The research method used is the ADDIE development model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 20 fourth grade students and involved design experts, material experts, media experts, and colleagues as validators. The results of validation from experts and trials on students showed that Wordwall-based learning media were included in the "very feasible" category for use in the learning process. This media is able to increase motivation, learning activities, and student learning outcomes. The advantages of this media lie in its attractive visual appearance, high interactivity, and suitability to the learning characteristics of elementary school students. This study recommends the use of Wordwall as an alternative media in thematic learning in elementary schools, as well as opening up opportunities for further development in various subjects and levels of education.